2018
DOI: 10.1111/cod.13009
|View full text |Cite
|
Sign up to set email alerts
|

Hand eczema in nurses, nursing auxiliaries and cleaners—A cross‐sectional study from a tertiary hospital in western India

Abstract: Hand eczema was particularly common in hospital cleaners and staff with atopic dermatitis. Further studies are needed to address the burden of occupational hand eczema and develop guidelines for its management at a national level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 36 publications
1
31
3
Order By: Relevance
“…A Swedish study involving 12,288 physicians, nurses and auxiliary nurses reported a prevalence of 21% (response rate 43%) (16), which was higher than the 10.8% seen in our study (response rate 80.2%) and that seen in Indian nurses (6.8%) (29). The incidence of hand eczema among nurses of our study was also lower than that of other Chinese City, including Harbin (19), Zhenjiang (20) and Shijiazhuang ( 21) cities.…”
Section: Discussioncontrasting
confidence: 79%
“…A Swedish study involving 12,288 physicians, nurses and auxiliary nurses reported a prevalence of 21% (response rate 43%) (16), which was higher than the 10.8% seen in our study (response rate 80.2%) and that seen in Indian nurses (6.8%) (29). The incidence of hand eczema among nurses of our study was also lower than that of other Chinese City, including Harbin (19), Zhenjiang (20) and Shijiazhuang ( 21) cities.…”
Section: Discussioncontrasting
confidence: 79%
“…After treatment, there was a 43.5% improvement in DLQI scores in construction workers, 55.2% in farmers, 43.4% in housewives and 80.0% improvement in healthcare workers. There was a statistically significant greater impairment in QoL in cleaners compared to nurses and nursing auxiliaries 16 . There were higher mean DLQI scores (indicating greater QoL impairment) among operating nurses compared to female administrative employees 33 .…”
Section: Resultsmentioning
confidence: 88%
“…From the 369 articles identified in the literature search, 328 were excluded based on the exclusion criteria, leaving 41 publications for the final analysis 12‐52 . The list of included publications and their characteristics are given in Table .…”
Section: Resultsmentioning
confidence: 99%
“…Globally, the point prevalence of hand eczema in the general population has been estimated at 4.0%, with a 1‐year prevalence of 9.1% and a lifetime prevalence of 14.5% 4 . The incidence of hand eczema is 7.3 cases per 1000 person‐years, 4 with certain occupations having higher incidence rates, including nursing, hairdressing and others that involve exposure to moisture 1,11–13 . In Germany, the epidemiological burden of hand eczema among the general population shows a large variation.…”
Section: Introductionmentioning
confidence: 99%